2017
DOI: 10.1002/mabi.201600495
|View full text |Cite
|
Sign up to set email alerts
|

Photoreversibility and Biocompatibility of Polydimethylsiloxane‐Coumarin as Adjustable Intraocular Lens Material

Abstract: Polydimethylsiloxane (PDMS) constitutes an interesting material for a variety of biomedical applications, especially as intraocular lenses (IOLs), for its excellent transparency. In this work, a photoreversible PDMS-coumarin network, whose shape and properties can be adjusted postoperatively in a noninvasive manner, is developed. The synthesis of PDMS-coumarin is achieved by amidation of a coumarin acid chloride derivative with amine-functionalized PDMSs. Under exposure of λ > 300 nm, these polymers can be cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…This represents better protection for the eyes. On this basis, Jellali et al (2017) synthesized a silicone-coumarin phototunable intraocular lens and tested the photosensitivity and biocompatibility. Ultraviolet-visible light spectroscopy showed that irradiation above 300 nm occurred crosslinking, and the process was reversed under light below 245 nm.…”
Section: Advances In Intraocular Lens Optical Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…This represents better protection for the eyes. On this basis, Jellali et al (2017) synthesized a silicone-coumarin phototunable intraocular lens and tested the photosensitivity and biocompatibility. Ultraviolet-visible light spectroscopy showed that irradiation above 300 nm occurred crosslinking, and the process was reversed under light below 245 nm.…”
Section: Advances In Intraocular Lens Optical Materialsmentioning
confidence: 99%
“… (A) Schematic of photoreversible crosslinking of PDSM-coumarin polymer. (B) Schematic of designed IOL from Jellali et al (2017) , with the permission of Wiley. …”
Section: Advances In Intraocular Lens Optical Materialsmentioning
confidence: 99%
“…The [2πs + 2πs] photocycloaddition of coumarin derivatives upon irradiation with UV light (>300 nm), to generate cyclobutane derivatives with itself or even with another double bond in the reaction medium, has been widely employed in the synthesis of polymeric networks [ 41 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ]. The advantages of this method are the creation of a network without extra monomers or photoinitiators [ 66 ] and the possibility to reverse the process (by regenerating the double bonds using radiation wavelength <290 nm).…”
Section: Photoreaction Mechanisms Of Coumarin and Its Derivativesmentioning
confidence: 99%
“…Diffusion of polymer chains against a photo-induced crosslinking gradient has been previously reported for the preparation of heterogeneously swollen lms. 50,51 Diffusion in our samples was studied using pulsed eld gradient (PFG) 1 H NMR spectroscopy. 52,53 The translational diffusion coefficient (D t ) and rotational time play important roles in crystallization events, governing the rates of mass transport and reorientation to the growing crystal facets respectively.…”
Section: Polymer Crystal Growth Mechanismmentioning
confidence: 99%